Soybean yield determinants and response to rhizobial inoculation in an onfarm trial in the northern Guinea savanna of Nigeria - Okogun, J.; Otuyemi, B.; Sanginga, P. (2004)
The response of two soybean varieties (Samsoy-2 and improved variety TGx 1448-2E) to Bradyrhizobium inoculation in the northern Guinea savanna of Nigeria was tested in a researcher-managed on-farm trial. There were variations in soybean yields between and within farmers fields. Data obtained from 24 farmers fields were analysed in a mixed model analysis of variance whereby the variance of the random component was estimated using Gausian restricted maximum likelihood. Five major soil components recognised to contribute to the yield determining factors of the soybean varieties were as follows: (a) effective cation exchange capacity (ECEC), (b) silt and phosphorus, (c) acidity (d) soil total nitrogen and (e) salinity.